Penggunaan Media Puzzle Pecahan dalam Meningkatkan Hasil Belajar Siswa Kelas III pada Pelajaran Matematika - Lubis, Luthfi Adam; Aina, Tasha; Wandini, Rora Rizky (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study is to identify the problems in learning Mathematics, simple fractions, educational learning media, and the learning outcomes of SDN 101873 Batang Kuis. This study uses qualitative research methods with observation techniques, literature analysis, and documentation when conducting learning activities in analyzing the use of fraction puzzles in the fraction material abilities at SDN 101873 Batang Kuis. The subjects of this study are third-grade students at SDN 101873 Batang Kuis. The results of implementing fraction puzzles in the fraction material skills at Batang Kuis show that mathematical puzzle skills have improved in the third grade. Students really enjoy playing fraction puzzles. Based on the results of the research and discussion, it can be concluded that the use of fraction puzzle media in fraction material provides a better impact. Students are able to first understand and analyze problems, able to design, plan, and find solutions, and then evaluate these solutions.